Forgiveness Pada Wanita Yang Mempunyai Anak Diluar Nikah - Bhawono, Satejo Aryo; , Dra. Rini Lestari, M.Si (2016)
A premarital childbearing woman has some choices about her pregnancy to be maintained or not? If it will be maintained, then she should think if she will marry or be a single parent and raise her child alone and she is trying to forgive her irresponsible partner. Purpose of the research is to know dynamics of forgiveness of woman with premarital child. Interview was used to collect data of the research. Informants of the research were unmarried 3 women with premarital children. Results of the research indicated that dynamics of forgiveness experienced by informant started with hatred toward her partner because of his irresponsible attitude for her pregnancy. Although the informant initially tried to do abortion, but finally she decided to maintain her pregnancy with reason that she should not make the mistake again. Informant tried to forget her past and she would not rehash mistakes of her partner. The informant did it for her development of her child in future. The Informant filled her days with study in university and worked for a living. In addition, there was an informant who started her life with new partner.